Setting condition of surge tank based on stability of hydro-turbine governing system considering nonlinear penstock head loss. (December 2019) - Zhu, Daoyi; Guo, Wencheng
Highlights: Model of HTGS considering nonlinear penstock head loss is established. SCST based on stability of HTGS is derived. Characteristics of setting condition of surge tank are analyzed. Effect mechanism of nonlinear penstock head loss on SCST is revealed. Abstract: In order to provide a basis for the setting of surge tank to achieve the safe and stable operation of hydropower station, this paper studies the setting condition of surge tank (SCST) based on stability of hydro-turbine governing system (HTGS) considering nonlinear penstock head loss. Firstly, the mathematical model of the HTGS considering nonlinear penstock head loss is established. Secondly, the SCST based on stability of HTGS considering nonlinear penstock head loss is derived by using Hopf bifurcation theory. Finally, the characteristics effects of SCST are analyzed. The effect mechanism of nonlinear penstock head loss on SCST is revealed by the comparative analysis of different SCSTs based on stability. The results indicate that the HTGS considering nonlinear penstock head loss is a third order nonlinear dynamic system. There are three inequality criterions for the SCST, and the third one is the controlling inequality criterion with the highest requirement and acts as a dominant role. The flow inertia time constant of penstock Twt 0 corresponding to the endpoint of inequality interval is denoted as [ Twt 0 ]. [ Twt 0 ] is the allowable value of Twt 0 . When Twt 0 is less than [ Twt 0 ], it is not necessary to set surge tank. To obtain a more accurate SCST, the penstock head loss and its nonlinear characteristic should be considered.